Evaluation of different aspersion equipment for the application of entomopathogenic nematodes - LARA-G., JUAN CARLOS; LÓPEZ-N., JUAN CARLOS (Revista Colombiana de Entomología, 2005)
“Royal Condor” garden (RCJ), “Royal Condor” traditional (RCT) and “Calimax Leo Cafetera” (CLC) sprayers were evaluated to determine the effect on viability and pathogenicity of Infective Juveniles (IJ) of Steinernema sp. (Rhabditida: Steinernematidae) under laboratory conditions, simulating the aspersion of this nematode in the control of the coffee berry borer, Hypothenemus hampei (Ferrari). Doses of 500,000 IJ/1.5 L of water were used for the aspersions. The CLC was evaluated at 20 and 40 psi. All the sprayers were evaluated with and without filters to observe if damage to IJs existed. The applications were made in 80-ml collection bottles. Later, in the same bottles and making four measurements each half hour, the number of live and dead IJs were counted in each application. Using the infection method in larvae of Galleria mellonella (L.), in multiwell boxes with paper filter the virulence of the IJs was evaluated after each application in a ratio of 10:1 (IJ:larva) at 24, 48 and 72 hours after the inoculation. The results of viability of IJs using the different equipment to apply them with and without filters at different pressures were statistically similar. These oscillated between 96.57%±0.10 for CLC (40 psi) with filters and 98.97% ± 0.08 for RCT without filters. The virulence of the IJs on the larvae of G. mellonella was not affected either, registering mortalities of 100% after 72 hours. The results indicate that it is possible to use the equipment evaluated here for the application of these nematodes without them undergoing deterioration in their action on the insects to which they are directed.